Revenue for Techies : Red, Yellow, Green Money - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
How are you generating revenue in your business or career. This lesson talks about consulting, salary and MRR including investing. Topics include: * Consulting * Salary * Investments * Autonomy vs Dependency * MRR (Monthly Recurring Revenue).